Diversity and Some Biological Aspects of Fishes in Lake Maybahr, Albuko Woreda, Ethiopia - Deng, Gatriay Tut (International Journal of Zoology, 2021)
Because fishes live in less-accessible habitats, their remarkable diversity is rarely appreciated. The fishery sector is growing rapidly worldwide with the intention of improving the livelihood in developing nations. Therefore, conservation and management of aquatic resources become eminent. Morphometric measurements of fishes are important tools in fish biology and fisheries assessment and conservation. Ethiopia is one of the developing countries with rich water resources. Although there are plenty of water bodies in the country, they are less explored for their ichthyofaunal documentation. Therefore, this study aimed to explore the diversity and some biological aspects of fishes in Lake Maybahr. The fish sample was collected from selected sampling sites using gill nets with varying mesh sizes. Fish identification was done in the field using relevant taxonomic keys. After identification, the total length (TL) and total weight (TW) of the specimens were measured to the nearest 0.1 cm and 0.1 g, respectively. After measurement, the samples were labeled and preserved in a 10% formalin solution. Two fish species were documented in the study area. The length-weight relationships indicated that both species (C. carpio and O. niloticus) exhibited allometric growth during the wet season. But C. carpio demonstrated an isometric growth in the dry season. The diversity index (H’ = 0.69) revealed that fish diversity in the current study is far less than the result reported in the other studies. The evenness index (J’ = 0.99) showed that each species is fairly represented by a number of individuals. The correlation coefficient value of length and weight parameters is statistically significant at a 1% significance level (s, R2 = 0.85). The mean FCF revealed that both fish species are in good health. Further study on local people’s perception, initiating fishing activities, and organizing and providing training to youth is recommended.